Application of the Jigsaw Method in Qiro'ah Learning at MTs Darul Ulum Kepuhdoko Tembelang Jombang | Penerapan Metode Jigsaw dalam Pembelajaran Qiro’ah di MTs Darul Ulum Kepuhdoko Tembelang Jombang - Baiq Tuhfatul Unsi; Siti Robiatun Muniroh (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The issue raised in this study is about learning qiro'ah using the jigsaw method as an innovative teaching method. Jigsaw is a collaborative learning method, which forms students to study in small groups consisting of 4 people by paying attention to the heterogeneity of students' ability levels, the teacher gives a jigsaw card containing material topics to be discussed by expert groups who will then be tasked with explaining the material to group members origin and each group presents the results of their discussion. The purpose of this study was to determine the application of the jigsaw method in learning qiro'ah and to identify the supporting and inhibiting factors. This research method uses case study qualitative research. The application of the jigsaw method in qiro'ah learning has supporting and inhibiting factors. The supporting factors are: 1. the expertise of the teacher who can guide students to understand the material, 2. the activeness of students in discussing and explaining to their group members. The inhibiting factors are 1) limited time in delivering material, because the application of the jigsaw method takes a long time, 2) An unsupportive environment, namely many students who live in an environment who do not have the habit of reading and writing Arabic, 3) Lack of interest in reading Arabic on students, 4). lack of mastery of Arabic vocabulary so that it is difficult to determine the meaning of sentences in the material read.